2013
DOI: 10.1007/s00221-013-3462-z
|View full text |Cite
|
Sign up to set email alerts
|

Crossmodal influences on early somatosensory processing: interaction of vision, touch, and task-relevance

Abstract: Previous research suggests that somatosensory cortex is subject to modulation based on the relevancy of incoming somatosensory stimuli to behavioural goals. Recent fMRI findings provide evidence for modulation of primary somatosensory cortex when simultaneous visual and tactile stimuli were relevant to the performance of a motor task. The present study aimed to (1) determine the temporal characteristics of this modulation using event-related potentials (ERPs) and (2) investigate the role of task-relevance in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 35 publications
7
25
1
Order By: Relevance
“…The prevailing thought on the generators of the N140 is that it reflects activation of prefrontal cortex, an area that is known to play a role in retrieving and maintaining representations of stimulus relevancy in relation to behavioral goals (Desmedt and Tomberg, 1989; Allison et al, 1991; Pardo et al, 1991; Knight et al, 1995), however, the bilateral distribution of the N140 at parietal sites has also prompted some researchers to suggest a generator in S2 (Frot and Mauguiere, 1999), which as mentioned previously has been implicated in attention to tactile stimuli. Similar to the current study, the results of Dionne et al (2013) also showed different patterns of N140 modulation at frontal and parietal sites and these results provide further support that this component might be associated with multiple generators such that the frontal and parietal generators are sensitive to different factors. Given the results of these two studies, it seems that the parietal component of the N140 shows specificity for task demands but not crossmodal stimuli, and the frontal component is sensitive to both crossmodal stimuli in addition to task requirements.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The prevailing thought on the generators of the N140 is that it reflects activation of prefrontal cortex, an area that is known to play a role in retrieving and maintaining representations of stimulus relevancy in relation to behavioral goals (Desmedt and Tomberg, 1989; Allison et al, 1991; Pardo et al, 1991; Knight et al, 1995), however, the bilateral distribution of the N140 at parietal sites has also prompted some researchers to suggest a generator in S2 (Frot and Mauguiere, 1999), which as mentioned previously has been implicated in attention to tactile stimuli. Similar to the current study, the results of Dionne et al (2013) also showed different patterns of N140 modulation at frontal and parietal sites and these results provide further support that this component might be associated with multiple generators such that the frontal and parietal generators are sensitive to different factors. Given the results of these two studies, it seems that the parietal component of the N140 shows specificity for task demands but not crossmodal stimuli, and the frontal component is sensitive to both crossmodal stimuli in addition to task requirements.…”
Section: Discussionsupporting
confidence: 90%
“…As such the amplitudes of the early components reported here will not be affected by the small difference in stimulus durations for the tactile stimuli presented in the uni- and bimodal conditions of Experiment 1. This is supported by the similarities of the waveforms, especially the consistent timing of the P50, P100, and N140 components in the unimodal and bimodal conditions reported in previous studies using these same parameters (Dionne et al, 2013; Popovich and Staines, 2014). In addition, in the case when the visual stimulus precedes the tactile stimulus by 100 ms (VT Grade) shown in Figure 6 (red trace) there is some indication of alpha-like activity.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations